1991
DOI: 10.1113/jphysiol.1991.sp018571
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology of dopaminergic and non‐dopaminergic neurones of the guinea‐pig substantia nigra pars compacta in vitro.

Abstract: SUMMARY1. The membrane properties of substantia nigra pars compacta neurones were studied using an in vitro slice preparation of guinea-pig midbrain.2. Neurones were divided into two classes based on their electrophysiological properties: bursting neurones displayed a burst of several rapidly accommodating action potentials in response to relaxation of hyperpolarizing current injected through the microelectrode, while non-bursting neurones produced regularly spaced action potentials. These neuronal types were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
195
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(222 citation statements)
references
References 39 publications
26
195
1
Order By: Relevance
“…2A). All these properties correspond to those of dopaminecontaining SN neurons demonstrated in previous studies (Grace and Onn, 1989;Yung et al, 1991), and to those of cells presumed to be dopamine-containing in other studies (such as Lacey et al, 1989;Riiper et al, 1990~;Johnson and North, 1992;see Lacey, 1993, for review). Thus, the cells studied here are considered to be dopamine neurons.…”
Section: Resultsmentioning
confidence: 87%
“…2A). All these properties correspond to those of dopaminecontaining SN neurons demonstrated in previous studies (Grace and Onn, 1989;Yung et al, 1991), and to those of cells presumed to be dopamine-containing in other studies (such as Lacey et al, 1989;Riiper et al, 1990~;Johnson and North, 1992;see Lacey, 1993, for review). Thus, the cells studied here are considered to be dopamine neurons.…”
Section: Resultsmentioning
confidence: 87%
“…The subthreshold Ca 2+ -K + oscillatory mechanism underlies the generation of low frequency background firing in a significant subpopulation of DA neurons [7][8][9][10][11][12][13][14][15][16][17][18]51]. However, a number of studies suggest a contribution of Ca 2+ -independent currents to oscillations [26,19,25,27,46].…”
Section: Influence Of Intrinsic Currents On the Type Of Excitabilitymentioning
confidence: 99%
“…The type of excitability is determined by the internal properties of the currents contributing to pacemaking in the DA neuron. L-type Ca 2+ and SK-type Ca 2+ -dependent K + currents are the core currents that traditionally constitute this mechanism [7][8][9][10][11][12][13][14][15][16][17][18] (but see the section on the mechanisms of DA neuron pacemaking). However, our model shows that the mechanism results in type II excitability, in which a hyperpolarizing current blocks the voltage oscillations without restoring a low frequency.…”
Section: The Role Of the Subthreshold Sodium Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…These neurons are spontaneously active with a mean firing rate around 30 Hz in anesthetized rats (Celada et al, 1999) and have axonal conduction velocities similar to pallidal neurons, around 3-4 m/s (Deniau et al, 1978;Guyenet and Aghajanian, 1978). 191 At one time it was believed that the nondopaminergic nigral neurons that were the source of the GABAergic input to the dopaminergic neurons were true local circuit neurons, leading them to be explicitly referred to as ''interneurons'' in the literature (e.g., Bunney, 1979, 1985;Mereu and Gessa, 1985;Araneda and Bustos, 1989;Yung et al, 1991;Zhang et al, 1993;Bontempi and Sharp, 1997). However, the neuroanatomical and electrophysiological properties reported for the putative pars reticulata GABAergic interneurons are not very different from those of antidromically identified nigrothalamic and nigrotectal projection neurons (Matsuda et al, 1987;Yung et al, 1991;Lee and Tepper, 2007 but see also Grace and Bunney, 1979;Grace et al, 1980) that have been shown to send axon collaterals to the pars compacta which synapse onto dopaminergic neurons Grofova et al, 1982;Hajos and Greenfield, 1993;Tepper et al, 1995Tepper et al, , 2002Mailly et al, 2003).…”
Section: Gabaergic Afferents To Nigral Dopaminergic Neuronsmentioning
confidence: 99%